3D-CT imaging processing for qualitative and quantitative analysis of maxillofacial cysts and tumors - Cavalcanti, Marcelo de Gusmão Paraiso (2002)
The objective of this study was to evaluate spiral-computed tomography (3D-CT) images of 20 patients presenting with cysts and tumors in the maxillofacial complex, in order to compare the surface and volume techniques of image rendering. The qualitative and quantitative appraisal indicated that the volume technique allowed a more precise and accurate observation than the surface method. On the average, the measurements obtained by means of the 3D volume-rendering technique were 6.28% higher than those obtained by means of the surface method. The sensitivity of the 3D surface technique was lower than that of the 3D volume technique for all conditions stipulated in the diagnosis and evaluation of lesions. We concluded that the 3D-CT volume rendering technique was more reproducible and sensitive than the 3D-CT surface method, in the diagnosis, treatment planning and evaluation of maxillofacial lesions, especially those with intra-osseous involvement.